Outcomes of trauma education workshop in Vietnam: improving diagnostic and surgical skills - Sugy Choi; Jieun Kim; Jongho Heo; Dung Thi Ngoc Nguyen; Son Hong Nguyen; Woong-Han Kim (BMC Medical Education, 2020)
Abstract Background Unintentional injuries have emerged as a significant public health issue in low- and middle-income countries (LMIC), especially in Vietnam, where there is a poor quality of care for trauma. A scarcity of formal and informal training opportunities contributes to a lack of structure for treating trauma in Vietnam. A collaborative trauma education project by the JW LEE Center for Global Medicine in South Korea and the Military Hospital 175 in Vietnam was implemented to enhance trauma care capacity among medical staff across Ho Chi Minh City in 2018. We aimed to evaluate a part of the trauma education project, a one-day workshop that targeted improving diagnostic and surgical skills among the medical staff (physicians and nurses). Methods A one-day workshop was offered to medical staff across Ho Chi Minh City, Vietnam in 2018. The workshop was implemented to enhance the trauma care knowledge of providers and to provide practical and applicable diagnostic and surgical skills. To evaluate the workshop outcomes, we utilized a mixed-methods survey data. All participants (n = 27) voluntarily completed the post-workshop questionnaire. Quality of contents, satisfaction with teaching skills, and perceived benefit were used as outcomes of the workshop, measured by 5-point Likert scales (score: 1–5). Descriptive statistics were performed, and open-ended questions were analyzed by recurring themes. Results The results from the post-workshop questionnaire demonstrated that the participants were highly satisfied with the quality of the workshop contents (mean = 4.32 standard deviation (SD) = 0.62). The mean score of the satisfaction regarding the teaching skills was 4.19 (SD = 0.61). The mean score of the perceived benefit from the workshop was 4.17 (SD = 0.63). The open-ended questions revealed that the program improved their knowledge in complex orthopedic surgeries neglected prior to training. Conclusions Positive learning experiences highlighted the need for the continuation of the international collaboration of skill development and capacity building for trauma care in Vietnam and other LMIC.